1999
DOI: 10.1093/jnci/91.20.1744
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Gene Delivery Using Recombinant Vaccinia Virus in a Rabbit Model of Liver Metastases

Abstract: Tumor-specific gene delivery is possible after systemic injection of a thymidine kinase-negative vaccinia virus vector in a model of rabbit liver metastases. Although the period of transgene expression appears limited because of a rapid immune response, the therapeutic window might be sufficient for an enzyme/prodrug gene therapy approach in clinical application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Futhermore, intravenous administration of the luciferase-expressing recombinant VV led to significantly higher luciferase activity in different tumor models compared to normal tissues assayed. 27,31 In our biodistribution studies, viral recovery from mouse tissues demonstrated that VV-FCU1 was consistently detected in all s.c. tumors whereas other organs remain much less infected. Our measurement of viral infection of organs is done 14 days after injection.…”
Section: Oncolytic Vaccinia Virus Expressing Fcu1 J Foloppe Et Almentioning
confidence: 75%
See 1 more Smart Citation
“…Futhermore, intravenous administration of the luciferase-expressing recombinant VV led to significantly higher luciferase activity in different tumor models compared to normal tissues assayed. 27,31 In our biodistribution studies, viral recovery from mouse tissues demonstrated that VV-FCU1 was consistently detected in all s.c. tumors whereas other organs remain much less infected. Our measurement of viral infection of organs is done 14 days after injection.…”
Section: Oncolytic Vaccinia Virus Expressing Fcu1 J Foloppe Et Almentioning
confidence: 75%
“…This was demonstrated in numerous tumor models, including murine colon cancer and melanoma, 27 murine and human ovarian tumors 30 and rabbit kidney cancer. 31 Infection and lysis of 100% of the cells in a tumor is difficult to achieve in vivo using oncolytic viruses alone. Therefore, oncolytic viruses are often 'armed' with enzyme-prodrug systems which are capable of exerting a strong bystander effect and which may enhance the oncolytic efficacy of the virus therapy by eliminating uninfected tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to compare these properties with the behavior of other gene delivery systems. In the case of viral vectors, there have been three reports of transgene expression in liver metastases and in a distal tumor following systemic administration of a recombinant vaccinia virus 18,19 and a selectively replicating adenovirus. 20 These viral vectors are replication incompetent in normal nondividing cells but can selectively replicate in tumor cells resulting in transgene expression in tumors and antitumoral efficacy.…”
Section: Figure 4 Toxicity Resulting From IV Injection Into Mice Ofmentioning
confidence: 99%
“…32 As demonstration of the selectivity and efficiency, we showed that this virus can be injected intravenously or intraperitoneally and be taken up into a subcutaneous tumor, replicate in the tumor, and lead to an antitumor response. 33 This effect is directly related to intratumoral vaccinia replication, and not a bystander inflammatory response.…”
Section: Cancer Gene Therapymentioning
confidence: 96%